An approach for annual analysis of EMF exposure in highly sensitive areas of kindergartens and schools - Kljajic, Dragan; Djuric, Nikola; Pasquino, Nicola; Solmonte, Nunzia; Djuric, Snezana (Radiation protection dosimetry, 2025)
Continuous increase of electromagnetic field (EMF) emission in the environment causes worldwide research on various short- and long-term EMF measurements and exposure assessments. Measurements are usually performed in sensitive areas, with conventional measuring approaches and worst-case exposure assessments, which are unable to provide any deeper EMF behavior analyses. Therefore, this paper brings an innovative EMF exposure analysis approach, based on time-averaging of time series data, disclosing some concealed information on long-term exposure. The averaging was done on the set of EMF time series acquired by three sensors in the EMF Regulatory Agency for Electronic Communications and Postal Services (RATEL) monitoring network. Sensors are installed at extremely sensitive locations-on buildings of two kindergartens and an elementary school. Analyses revealed patterns of daily/weekly exposure changes and their differences between working days and weekends, as well as annual decrease/increase, at each location. Comparative analysis among locations showed differences in exposure behavior regarding its peaks, slopes of the decrease/increase, and time intervals of the day with higher exposure.